2014
DOI: 10.1093/annhyg/meu038
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Therapeutic Proteins by Inhalation—Worker Safety Aspects

Abstract: A literature review and analysis of inhalation bioavailability data for large therapeutic proteins was conducted in order to develop a practical estimate of the inhalation bioavailability of these drugs. This value is incorporated into equations used to derive occupational exposure limits(OELs) to protect biopharmaceutical manufacturing workers from systemic effects. Descriptive statistics implies that a value of 0.05, or 5% is an accurate estimate for large therapeutic proteins (molecular weight ≥ 40kDa). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…HCPs who have graduated more recently may therefore have a greater understanding of the inherent properties of these large molecules, which in general are minimally hazardous through routine occupational exposures due to negligible bioavailability through oral inhalation or dermal absorption. 24 , 25 This may also be why they are less likely to use CSTDs with all oncology biologics than their counterparts with more than 15 years of experience.…”
Section: Discussionmentioning
confidence: 99%
“…HCPs who have graduated more recently may therefore have a greater understanding of the inherent properties of these large molecules, which in general are minimally hazardous through routine occupational exposures due to negligible bioavailability through oral inhalation or dermal absorption. 24 , 25 This may also be why they are less likely to use CSTDs with all oncology biologics than their counterparts with more than 15 years of experience.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the general instability of biologic therapeutics, differences in their manufacturing (generally closed processes to protect sterility) and their potential limited bioavailability (BA) via the inhalation, oral and dermal routes ( Gould et al, 2018 ; Pfister et al, 2014a ; Bos and Meinardi, 2000 ; Krause and Sahin, 2019 ), it can be argued that a different set of exposure controls can be utilized to protect employees when working with biologics as compared to small molecules. Based on this information as well as extensive industrial hygiene monitoring conducted by BMS showing that airborne concentrations of biologics are most often <1 μg/m 3 (data not shown), a simplified two-band system was developed for biologics for use when there is insufficient information available to calculate an OEL.…”
Section: Occupational Exposure Control Bandingmentioning
confidence: 99%
“…For peptides where there is no target in the lung, the inhalation route would be less of a concern, although inhalation BA would still need to be considered. An evaluation of inhalation studies with peptides conducted by Pfister et al (2014) reported BAs of up to 100%, with most being <50% ( Pfister et al, 2014a ).…”
Section: Occupational Exposure Control Banding Considerations For Phamentioning
confidence: 99%
See 1 more Smart Citation